The Association Between Test Anxiety, Self-Efficacy, and Mental Images Among University Students: Results From an Online Survey - Maier, Anna; Schaitz, Caroline; Kröner, Julia; Berger, Alexander; Keller, Ferdinand; Beschoner, Petra; Connemann, Bernhard; Sosic-Vasic, Zrinka (Frontiers in Psychiatry, 2021)
Background and objectives: A substantial portion of students report test anxiety, and those reporting low levels of self-efficacy seem to be especially affected. Previous research has indicated the relevance of mental images in the maintenance of anxiety disorders, however, no data are available with respect to test anxiety. In order to close this gap, the present study investigates the association between test anxiety, self-efficacy and mental images. Method: 163 university students completed an online survey. Test anxiety (PAF), general self-efficacy (WIRKALL-r), study-related self-efficacy (WIRK_STUD), intrusiveness of mental images (IFES), spontaneous use of imagery (SUIS) and vividness of imagery (VVIQ) were examined. Results: Test-related mental images were frequently reported among the surveyed students. Test anxiety showed a positive correlation with IFES and self-efficacy. The path-analysis showed significant main effects for IFES and SUIS, but no significant interaction with WIRK_STUD. Partial correlations indicated a decreased association between self-efficacy and test anxiety after controlling for test-related mental images. Discussion: The present study gives first indication about an association between test anxiety, self-efficacy and mental images, even though the results are limited with respect to generalizability. Further investigations with respect to the impact of test-related mental images on the self-efficacy/test-anxiety linkage are needed.